ROAD RUNNING: WHAT MOTIVATE RUNNERS OF DIFFERENT AGES? (Fiep Bulletin - online, 2020)
The road running has been increasing the number of fans each day, reaching the public of men and women of different ages. Among the benefits of the race are the ease of access and the consequences of regular practice, such as stress control, reduction of the body fat percentage, improved sleep quality, among other aspects related to quality of life. Understanding the reasons for adherence and attendance to the practice of running is important for professionals working in this area. The objective of this study was to verify the motivational factors for the practice of road running among runners of different age groups. For the study, 56 road runners were divided into three groups: adult adolescent (AA, age less than 30 years old, n= 16), young adult (AJ, aged 30 to 40 years, n= 24) and middle-aged (MI, older than 40 years, n= 16). The Inventory of Motivation Questionnaire was used for the regular practice of physical exercise (IMPRAF-54) applied online. We found that the AJ and MI groups show similar behaviors among the evaluated runners. When comparing the AA and MI groups, we found that the group with the highest age group presented higher values ??for stress control and sociability. Road runners, regardless of age, practice the sport motivated by aspects related to health and pleasure. In addition, group MI practices running motivated to a greater degree by sociability and stress control when compared to group AA.
Keywords: Road Running; IMPRAF-54; Motivation